Utilization potential of low temperature hydronic space heating systems in Russia. (September 2017) - Ovchinnikov, Petr; Borodiņecs, Anatolijs; Millers, Renārs
Abstract: Due to drastically tightened building regulations in Europe in recent years, there has been gradual transfer to low-exergy heating systems in housing stock. Practices that take place in northern countries with similar to Russia weather conditions such as Denmark, Sweden and Finland showed apparent potential in applying such systems in Russia. The latest changes and tendencies in building legislation system here although try to introduce low-exergy systems in local market still confront it indirectly. The current study aims at evaluating practical application of low temperature hydronic space heating systems in residential buildings in Russia with a view to current recommendations on thermal performance of a building. Study object was placed in different locations of the country with corresponding to these locations envelope properties. Mathematical model was calculated using the energy simulation tool IDA Indoor Climate and Energy (ICE) 4.7. Parameters of comfort and energy performance were evaluated for every studied configuration. Results show partial applicability of low-temperature hydronic space heating systems with correspondence to current regulations on building's U-values. Possible measures of improvement were proposed in order to achieve good thermal comfort in every studied configuration. Highlights: Application of low-temperature space heating in Russia. Simulation analysis with different configurations of low temperature hydronic space heating was conducted. Analysis of thermal comfort. Application of low temperature heating in buildings that are insulated according to Russian regulations is limitedly possible. Ways of improvement of thermal performance were proposed.